Asperidines A–C, pyrrolidine and piperidine derivatives from the soil-derived fungus Aspergillus sclerotiorum PSU-RSPG178 - Patima Phainuphong (2019)
© 2018 Elsevier Ltd One new pyrrolidine derivative, asperidine A (1), and two new piperidine derivatives, asperidines B (2) and C (3), were isolated from the soil-derived fungus Aspergillus sclerotiorum PSU-RSPG178 together with two known alkaloids. Compound 3 possessed an unprecedented 7-oxa-1-azabicyclo[3.2.1]octane skeleton with four chiral centers. Their structures were determined by spectroscopic evidence. The absolute configurations of compounds 2 and 3 were established using Mosher's method and further confirmed for compound 3 by X-ray crystallographic data. Compound 2 dose-dependently inhibited the CFTR-mediated chloride secretion in T84 cells with an IC50 value of 0.96 μM whereas 3 displayed the same activity with the IC50 value of 58.62 μM. Compounds 2 and 3 also significantly reduced intracellular ROS under both normal and H2O2-treated conditions compared with their respective controls in a dose-dependent manner without cytotoxic effect on Caco-2 cells. In addition, compound 3 was inactive against noncancerous Vero cells whereas compound 2 was considered to be inactive with the IC50 value of >10 μM.